2018
DOI: 10.1021/acs.joc.8b01780
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of Flavylium Salts as a Valuable Tool To Design the Synthesis of A-Type Proanthocyanidin Analogues

Abstract: A convenient method to synthesize A-type proanthocyanidin analogues from flavylium salts and π-nucleophiles has been developed. It was found that the thermodynamic stability of the starting flavylium salt, assessed by the measurement of the apparent acidity constant ( K'), was the key parameter to design effective one-pot reactions between flavylium salts and nucleophiles such as phloroglucinol and (+)-catechin. When flavylium salts have a p K' value of 1.7 or lower, the synthesis of the corresponding 2,8-diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…The design of these smart nanocarriers requires an appropriate selection of the type of nanocarrier, targeting mechanisms to locate specific cells and stimulus techniques to release the drug inside. In this field, our research group is making some efforts in terms of design and synthesis of chitosan-modified polymeric micelles for targeting hepatocytes [ 182 ]. For that, two hepatocyte cell features have been taken into account: (a) the high expression level on hepatocytes of asialoglycoprotein receptors (ASGPR) vs minimal expression on extrahepatic cells [ 175 , 183 ]; (b) the different concentration of glutathione (GSH) in blood plasma (10µM) vs hepatic cells (10 mM) [ 177 ].…”
Section: Enzyme Inhibitors For the Treatment Of Phsmentioning
confidence: 99%
“…The design of these smart nanocarriers requires an appropriate selection of the type of nanocarrier, targeting mechanisms to locate specific cells and stimulus techniques to release the drug inside. In this field, our research group is making some efforts in terms of design and synthesis of chitosan-modified polymeric micelles for targeting hepatocytes [ 182 ]. For that, two hepatocyte cell features have been taken into account: (a) the high expression level on hepatocytes of asialoglycoprotein receptors (ASGPR) vs minimal expression on extrahepatic cells [ 175 , 183 ]; (b) the different concentration of glutathione (GSH) in blood plasma (10µM) vs hepatic cells (10 mM) [ 177 ].…”
Section: Enzyme Inhibitors For the Treatment Of Phsmentioning
confidence: 99%
“…75 Our further studies allowed us to correlate the reactivity between a flavylium salt with π nucleophiles [i.e., phloroglucinol and (+)-catechin] with the constant K′ a of the flavylium salt and, hence, validate our initial hypothesis (Scheme 14). 72 It was observed that, when flavylium salts have a pK′ a value of 1.3 or lower, Kraus' conditions (methanol and 50 °C) may be useful to achieve the synthesis of bicyclic derivatives. However, for flavylium salts with a pK′ a value of 2.8 or higher, a microwave methodology should be used to achieve, in some cases, the reaction between these flavylium salts and the nucleophiles (Scheme 14).…”
Section: ■ Synthesis Of A-type Pac Analoguesmentioning
confidence: 99%
“…However, for flavylium salts with a pK′ a value of 2.8 or higher, a microwave methodology should be used to achieve, in some cases, the reaction between these flavylium salts and the nucleophiles (Scheme 14). 72 In addition, our research group has evaluated the antimicrobial and antibiofilm properties of a selection of 2,8dioxabicyclo[3.3.1]nonane derivatives previously synthesized by us (54, 55, 61, and 66) 73 and compared the values obtained for two natural PACs [(+)-procyanidin B-2 and (+)-cinnamtannin B-1], also isolated by us from laurel wood, 76 and for commercial (+)-procyanidin A-2. This study improved the knowledge about the structural features that may have some influence on the antimicrobial and antibiofilm activities of Atype PAC analogues against foodborne pathogens: (i) the presence of electron-withdrawing groups at ring A or C instead of hydroxyl groups enhance activities (54, 55, and 66, versus 61), and (ii) the smaller size of the bottom monomer also enhances the effectiveness of the derivatives (54, 55, and 61, versus 66).…”
Section: ■ Synthesis Of A-type Pac Analoguesmentioning
confidence: 99%
See 2 more Smart Citations